Pengaruh Geometri Jalan Tambang Terhadap Produksi Alat Angkut Tambang Batubara PT Hillconjaya Sakti Jobsite Sebuku Tanjung Coal, Kecamatan Pulau Laut Tengah, Kabupaten Kotabaru, Provinsi Kalimantan Selatan - Ahmad Heriansyah; Iswandaru; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Hillconjaya Sakti is a mining contractor company whose job is to strip coal and overburden with an overburden production target of 291.937 BCM/month on one of the PC 2000 excavator loaders with actual production of 266.043 BCM/month. The problem in this study is the design of the overburden stripping haul road which is not ideal causing less than optimal productivity. So it is necessary to evaluate the geometry of the road which aims to determine the ideal haul road design, compare the target production of the conveyance with production after repair and find out the cycle time of the conveyance in overburden hauling activities .The research was conducted in the overburden area from front loading to disposal at South T3 Pit with HD Sanyi SRT 95C conveyor with a capacity of 42 m2. The data collected is crossslope, superelevation and maximum speed of the conveyance under certain road grade conditions and also the T-junctions formed on the haul road.. In the research results there are many road segments that have not reached the ideal criteria in road geometry, especially in the front loading area. The results of calculating the ideal geometry are 21,33 m for one lane, 25,55 m for bends, 1,02 m super elevation and 42,6 cm crossslope. The results of road repairs will cause a decrease in the circulation time or cycle time of the transportation equipment, there is a change in the cycle time of the transportation equipment, namely 13,97 minutes, 14,3 minutes, 14,02 minutes, 14,05, 14,2 minutes to 10,48 minutes so there was an increase in the production of transportation equipment to 336.982 BCM/month. Abstrak. PT Hillconjaya sakti merupakan perusahaan kontraktor penambangan yang bertugas dalam melakukan pengupasan batubara dan overburden dengan target produksi overburden sebesar 291.937 BCM/bulan pada salah satu alat muat excavator PC 2000 dengan produksi aktual 266.043 BCM/bulan. Permasalahan dalam penelitian ini adalah perancangan pada jalan angkut pengupasan overburden yang tidak ideal menyebabkan produktivitas kurang optimal. Maka perlu dilakukan evaluasi geometri jalan yang bertujuan untuk melakukan penentuan rancangan jalan angkut ideal, melakukan perbandingan target produksi alat angkut dengan produksi setelah perbaikan dan Mengetahui cycle time dari alat angkut pada kegiatan pengangkutan overburden.. Penelitian dilakukan pada area overburden dari front loading ke disposal di Pit T3 Selatan dengan alat angkut HD Sanyi SRT 95C dengan kapasitas 42 m2. Data yang dikumpulkan adalah data crossslope, superelevasi serta kecepatan maksimal alat angkut dalam kondisi grade jalan tertentu dan juga pertigaan yang terbentuk pada jalan angkut.. Pada hasil penelitian terdapat banyak segmen jalan yang belum mencapai dari kriteria ideal pada geometri jalan khusus nya pada daerah front loading. Hasil dari perhitungan geometri ideal yaitu 21,33 m untuk satu jalur,jalur tikungan 25,55 m, superelevasi 1,02 m dan crossslope 42,6 cm. Hasil perbaikan jalan akan menyebabkan penurunan waktu edar atau cycle time alat angkut, terjadi perubahan cycle time alat angkut yaitu 13,97 menit, 14,3 menit, 14,02 menit, 14,05, 14,2 menit menjadi 10,48 menit sehingga terjadi peningkatan produksi alat angkut menjadi 336.982 BCM/Bulan.